Utilizing on‐ and off‐line monitoring tools to follow a kinetic resolution step during flow synthesis. (11th August 2016) - Farley, Kathleen A.; Reilly, Usa; Anderson, Dennis P.; Boscoe, Brian P.; Bundesmann, Mark W.; Foley, David A.; Lall, Manjinder S.; Li, Chao; Reese, Matthew R.; Yan, Jiangli
Abstract: In situ reaction monitoring tools offer the ability to track the progress of a synthetic reaction in real time to facilitate reaction optimization and provide kinetic/mechanistic insight. Herein, we report the utilization of flow NMR, flow IR, and other off‐line spectroscopy tools to monitor the progress of a flow chemistry reaction. The on‐line and off‐line tools were selected to facilitate the stereoselective kinetic resolution of a key racemic monomer, which lacked a chromophore, making conventional reaction monitoring difficult. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In situ reaction monitoring tools offer the ability to track the progress of a synthetic reaction in real time to facilitate reaction optimization and provide kinetic/mechanistic insight. Herein, we report the utilization of flow NMR, flow IR, and other off‐line spectroscopy tools to monitor the progress of a flow chemistry reaction. The on‐line and off‐line tools were selected to facilitate the stereoselective kinetic resolution of a key racemic monomer, which lacked a chromophore, making conventional reaction monitoring difficult.